Diversity and Abundance of Insect Pollinators in Different Agricultural Lands in Jambi, Sumatera - Elida Hefni Siregar; Tri Atmowidi; Sih Kahono (Bogor Agricultural University, Indonesia, 2016)
Agricultural land use is an artificial ecosystem. Insect pollinators are important keys to success of the agroecosystem. Converting natural landscapes to agricultural land, such as oil palm and rubber plantations, affects the insects. The research aims to study diversity and abundance of insect pollinators in three different agricultural land uses, i.e. oil palm plantation, rubber plantation, and jungle-rubber. Scan sampling method was used to explore the diversity of insect pollinators. Observations of the insects were conducted from 08.00 to 10.00 AM and 02.00 to 04.00 PM in sunny days. There were 497 individuals of insect pollinators collected, which belong to 43 species in three orders (Hymenoptera, Diptera, and Lepidoptera). Number of species and individual of insect pollinators found in rubber plantations (31 species, 212 individuals) and oil palm plantation (23 species, 188 individuals) were higher than that in jungle rubber (7 species, 97 individuals). Insect pollinators in oil palm plantations were dominated by giant honey bee (Apis dorsata) and stingless bee (Trigona sp. [=aff. T. planifrons]), whereas in rubber plantation, they were dominated by small carpenter bees (Ceratina lieftincki and Ceratina simillima), and in jungle-rubbers were dominated by hoverfly (Syrphid sp.) and Apis andreniformis. Higher foraging activities of insect pollinators occured in the morning.